Analysis of the Ratio of Strategic Health Workers (Specialist Doctors) to Bed Capacity: HR Distribution Mapping and Its Implications for Hospital Talent Management in Indonesia - Hairudin La Patilaiya (Journal of Health Service Administration and Hospital Management, 2025)
This study investigates the distribution of specialist doctors relative to hospital bed capacity (DS/TT Ratio) across Indonesian provinces and explores its implications for hospital talent management strategies. The current healthcare landscape in Indonesia exhibits a significant gap; while hospital bed capacity has increased by approximately 12% annually, specialist recruitment has stagnated at 3.5%, leading to critical workload imbalances. Unlike population-based metrics, the DS/TT Ratio provides a more precise measure of clinical demand. Using quantitative analysis of official secondary data (2020–2024), this research maps geographic disparities and correlates them with socio-economic factors. Results reveal extreme spatial disparities: the national average ratio is 10.5 per 100 beds, but ranges from 23.20 in DKI Jakarta to only 4.40 in West Papua. A strong positive correlation (Spearman's  ) between the DS/TT Ratio and Gross Regional Domestic Product (GRDP) per capita identifies economic attractiveness as the primary driver of maldistribution. To address these disparities, this study provides strategic recommendations for stakeholders: the Ministry of Health should integrate DS/TT standards into hospital accreditation, while regional governments must utilize these ratios to justify targeted fiscal incentives and "service-bound" scholarship placement. By shifting the talent management paradigm from population-based to workload-based allocation, Indonesia can better address market failures in specialist distribution and ensure equitable access to quality care.